Aberrant FGF signaling promotes granule neuron precursor expansion in SHH subgroup infantile medulloblastoma - Odessa R Yabut; Jessica Arela; Hector G Gomez; Jesse Garcia Castillo; Thomas Ngo; Samuel J Pleasure (eLife)
Mutations in Sonic Hedgehog (SHH) signaling pathway genes, for example, Suppressor of Fused (SUFU), drive granule neuron precursors (GNP) to form medulloblastomas (MBSHH). However, how different molecular lesions in the Shh pathway drive transformation is frequently unclear, and SUFU mutations in the cerebellum seem distinct. In this study, we show that fibroblast growth factor 5 (FGF5) signaling is integral for many infantile MBSHH cases and that FGF5 expression is uniquely upregulated in infantile MBSHH tumors. Similarly, mice lacking SUFU (Sufu-cKO) ectopically express Fgf5 specifically along the secondary fissure where GNPs harbor preneoplastic lesions and show that FGFR signaling is also ectopically activated in this region. Treatment with an FGFR antagonist rescues the severe GNP hyperplasia and restores cerebellar architecture. Thus, direct inhibition of FGF signaling may be a promising and novel therapeutic candidate for infantile MBSHH.